Statistical Modeling of the Factors of Formation of the Quality of Employment in Ukraine - Korepanov Oleksiy S.; Lazebnyk Iuliia O.; Momotiuk Liudmyla Ye.; Parfentseva Nelya O.; Chala Tеtyana G.; Korepanov Georgii S.; Chernenko Daryna I. (Bìznes Inform, 2022)
In the article, the main attention is paid to the development of methodological principles of statistical modeling of factors for the formation of employment quality. The necessity of developing a new strategy in the formation of employment quality to ensure effective socioeconomic development of Ukraine is substantiated. The necessary steps and management decisions are determined. The problems of assessing the quality of employment in Ukraine are outlined, the main stage of which is the modeling of factors for the formation of employment quality using modern statistical methods. In order to define the generalized factors of employment quality formation, a model of the main components is constructed, allowing to transform the 18-dimensional sign space into a five-dimensional space of generalized factors that explain 87.6% of the variation in the selected features, which indicates a high level of factorization. Five main factors are identified and ranked according to the degree of importance: the level of informatization of society (contribution – 41.7%), working conditions and the environment (26.3%), informal employment (8.2%), industrial injuries with fatal consequences (6.3%), and the employment rate (5.1%). The computations were carried out using the application package «Statistica», in particular the module «Factor analysis». The use of the developed model makes it possible to prevent subjectivism in determining the main factors in the formation of employment quality. The conducted study provided to substantiate the theoretical-methodological principles of statistical modeling of factors for the formation of employment quality on the basis of the method of the main components. The identified factors can be taken as a basis for the formation of key directions of improvement of the employment sphere in Ukraine.